Blended Counseling to Reduce Career Anxiety of Adolescents during The COVID-19 Era - Kurniawan, Shopyan Jepri; Purwanta, Edi; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (COUNS-EDU: The International Journal of Counseling and Education, 2021)
The purpose of this paper is to discuss the development of blended-based counseling services to reduce anxiety in adolescents during the COVID-19 pandemic. The important role of counselors in the formation of mental health through integrated counseling the implementation of face-to-face and online counseling allows the community to be more flexible and intensive according to conditions in coaching mental health during COVID-19 pandemic conditions and post-COVID-19 preparations..